Environmental Tobacco Smoke During the Early Postnatal Period of Mice Interferes With Brain 18 F-FDG Uptake From Infancy to Early Adulthood – A Longitudinal Study - Torres, Larissa Helena; Real, Caroline Cristiano; Turato, Walter Miguel; Spelta, Lídia Wiazowski; dos Santos Durão, Ana Carolina Cardoso; Andrioli, Tatiana Costa; Pozzo, Lorena; Squair, Peterson Lima; Pistis, Marco; de Paula Faria, Daniele; Marcourakis, Tania (Frontiers in Neuroscience, 2020)
Exposure to environmental tobacco smoke (ETS) is associated with high morbidity and mortality, mainly in childhood. Our aim was to evaluate the effects of postnatal ETS exposure in the brain 2-deoxy-2-[18F]-fluoro-D-glucose (18F-FDG) uptake of mice by positron emission tomography (PET) neuroimaging in a longitudinal study. C57BL/6 J mice were exposed to ETS that was generated from 3R4F cigarettes from postnatal day 3 (P3) to P14. PET analyses were performed in male and female mice during infancy (P15), adolescence (P35), and adulthood (P65). We observed that ETS exposure decreased 18F-FDG uptake in the whole brain, both left and right hemispheres, and frontal cortex in both male and female infant mice, while female infant mice exposed to ETS showed decreased 18F-FDG uptake in the cerebellum. In addition, all mice showed reduced 18F-FDG uptake in infancy, compared to adulthood in all analyzed VOIs. In adulthood, ETS exposure during the early postnatal period decreased brain 18F-FDG uptake in adult male mice in the cortex, striatum, hippocampus, cingulate cortex, and thalamus when compared to control group. ETS induced an increase in 18F-FDG uptake in adult female mice when compared to control group in the brainstem and cingulate cortex. Moreover, male ETS-exposed animals showed decreased 18F-FDG uptake when compared to female ETS-exposed in the whole brain, brainstem, cortex, left amygdala, striatum, hippocampus, cingulate cortex, basal forebrain and septum, thalamus, hypothalamus and midbrain. The present study shows that several brain regions are vulnerable to ETS exposure during the early postnatal period and these effects on 18F-FDG uptake are observed even a long time after the last exposure. This study corroborates our previous findings, strengthening the idea that exposure to tobacco smoke in a critical period interferes with brain development of mice from late infancy to early adulthood.